KONSTRUKSI MEDIA TERHADAP TRANSGENDER - Fitri Meliya Sari (Professional: Jurnal Komunikasi dan Administrasi Publik, 2016)
This research was a study conducted on transgender as one of the media spotlight. This study aimed to describe how the media portrays the existence of transgender in Indonesia through media. In this case the researchers looked at the cases of Dena Rachman. Results showed that there was particular justification of media in portraying negatively the behavior of people who become transgender or the like. The portrayal makes people against for the decision and behavior taken by Dena Rachman. Changing the male identity to be a female is very unusual. Especially for those who think that identity is inherent and unchangeable. Yet this identity is socially constructed and liquid. Dena Rachman’a changing reinforces the notion that gender is only two, namely men and women.  Keywords: Transgender, Mass Media, Social Construction.